Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s12028-011-9508-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of Endothelin-1 in Human Aneurysmal Subarachnoid Hemorrhage: Associations with Vasospasm and Delayed Cerebral Ischemia

Abstract: Background Endothelin-1 (ET-1) is a potent vasoconstrictor implicated in the pathogenesis of vasospasm and delayed cerebral ischemia (DCI) in aneurysmal subarachnoid hemorrhage (aSAH) patients. The aim of this study was to investigate the relationship between cerebrospinal fluid (CSF) ET-1 levels and angiographic vasospasm and DCI. Methods Patients with aSAH were consented (n = 106). Cerebral vasospasm was determined by angiography. DCI was determined by transcranial Doppler (TCD) results and/or angiogram re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 41 publications
(33 reference statements)
3
27
0
1
Order By: Relevance
“…Catalytically active ECE-1 in CSF can convert BigET-1 to the potent vasoconstrictor ET-1. Previous studies have demonstrated the presence of both BigET-1 and ET-1 in CSF of SAH subjects (6), and an association between ET-1 and cerebral vasospasm has previously been shown (7). In this light, our discovery of soluble ECE-1 in CSF of SAH subjects indicates that the production of ET-1 can in fact occur in the CSF space.…”
Section: Resultssupporting
confidence: 58%
“…Catalytically active ECE-1 in CSF can convert BigET-1 to the potent vasoconstrictor ET-1. Previous studies have demonstrated the presence of both BigET-1 and ET-1 in CSF of SAH subjects (6), and an association between ET-1 and cerebral vasospasm has previously been shown (7). In this light, our discovery of soluble ECE-1 in CSF of SAH subjects indicates that the production of ET-1 can in fact occur in the CSF space.…”
Section: Resultssupporting
confidence: 58%
“…ET-1, a potent vasoconstrictor, is associated with both vasospasm resulting from SAH and delayed cerebral ischemia [48]. Elevated CSF levels of this cytokine have been correlated with pathologies observed after cerebral hemorrhage in humans [49] as well as in animal model [50].…”
Section: Discussionmentioning
confidence: 99%
“…Endothelin-1, a potent cerebral vasoconstrictor, has been strongly implicated in early brain injury, CVS, and ultimately DCI following aneurysmal SAH. 3,29,36,37,39,46,48,[50][51][52][53]75,79,86 Studies evaluating endothelial function in erectile dysfunction and pulmonary hypertension have demonstrated that sildenafil substantially reduces endothelin-1 levels. 44,60,64,65 The development of platelet-induced microthrombi within the microvasculature has also been implicated in DCI, [20][21][22]63,70 and sildenafil has been shown to limit this prothrombotic cascade.…”
Section: Sildenafil As Treatment For DCImentioning
confidence: 99%